Profile of Malassezia Folliculitis - Dwi Nurwulan Pravitasari; Sunarso Suyoso; Evy Ervianti (Faculty of Medicine, Universitas Airlangga, 2015)
Background: Malassezia folliculitis (MF) is a chronic infection of the pilosebaceous follicles caused by a skin fungus Malassezia sp. most often in teenagers who marked the onset of itchy erythematous perifolicular papules and pustules, especially in the upper body area and rarely on the face. The clinical appearance must be distinguished from acne vulgaris which has a similar clinical picture, so often have the wrong diagnosis that will affect the prognosis of the disease. Objective: To evaluate the profile of MF in Dermatology and Venereology Outpatient Clinic Dr. Soetomo General Hospital. Methods: A cross-sectional, observational, descriptive study, total samplingin three months of forty-five new patients with acne vulgaris appearance visiting Dermatology and Venereology Outpatient Clinic Dr. Soetomo General Hospital according to inclusion and exclusion criteria. Diagnosis based on history, clinical examination, Wood's lamp and KOH 20%. Malassezia sp. identification using Mycobiotic culture that is added to the olive oil. Results: Forty five patients with a clinical appearance of acne vulgaris in the upper body and slightly exposed on the face area, the new MF patients showed a total of 36 patients (80%) and the remaining 9 patients (20%) were diagnosed with acne vulgaris. Conclusions:Thirty six MF patients with the highest age range 15-24 years, anamnesis obtained itching is moderate grade, predilection in the area of the upper body, and Wood's Lamp examination produces greenish yellow color, KOH 20% examination obtained spores, whereas culture is not required for the diagnosis of MFKey words: Malassezia sp., Malassezia folliculitis, acne vulgaris, Wood's lamp, KOH 20%.